The Top 100 Highly Cited Original Articles on Immunotherapy for Childhood Leukemia - Zhong, Qing; Li, Bing-Hui; Zhu, Qi-Qi; Zhang, Zhi-Min; Zou, Zhi-Hao; Jin, Ying-Hui (Frontiers in Pharmacology, 2019)
Background: Childhood leukemia is one of the most common cancers in children. As a potential treatment for leukemia, immunotherapy has become a new research hotspot. This research aimed at exploring the status and trends of current researches on immunotherapy for childhood leukemia through bibliometric analysis. Methods: The Institute for Scientific Information Web of Science core collection database was searched for articles on immunotherapy and childhood leukemia using a computer. Time period for retrieval was from the beginning of the database to June 15, 2019. The top 100 highly cited articles were selected to extract their information on publication year, authors, title, publication journal, number of citations, author’s affiliations, country, and so on. These general information and bibliometric data were collected for analysis. VOSviewer software was used to generate a figure for keywords’ co-occurrence network and a figure for researcher’s coauthorship network that visualized reference and cooperation patterns for different terms in the 100 articles. Results: The number of citations in the top 100 articles ranged from 17 to 471. These articles were published in 52 different publications. The top four journals in terms of the number of our selected articles were Leukemia (11 articles), Blood (10 articles), Bone Marrow Transplantation (6 articles), and Clinical Cancer Research. The most frequently nominated author was T. Klingebiel from Goethe University Frankfurt, and of the top 100 articles, 12 listed his name. These top 100 articles were published after the year 2000. Most of these articles were original (67%). The United States and Germany were the major countries researching immunotherapy for childhood leukemia and made significant contributions to the combat against the disease. Adoptive immunotherapy and stem cell transplantation appeared more frequently in keywords. Conclusions: This study analyzed the top 100 highly cited articles on immunotherapy for childhood leukemia and provided insights into the features and research hotspots of the articles on this issue.